New insights into ancestry and health of Polynesians and New Zealand Māori - Chambers, Geoffrey; Edinur, Hisham; Dunn, Paul (New Zealand Science Review, 2016)
We are now moving towards the new era of personalised medicine. In prospect, a DNA-tailored healthcare system will utilise genomic information from patients and populations for the prevention and treatment of diseases. This near-future medicine recognises that there is already evidence of genetic disparity between people of different ethnicity. Our own previous genetic surveys of human genomes have demonstrated abundant genetic variation in New Zealanders. These now include extensive new work on immune system genes. We have produced a comprehensive reference set of genotypes for clinically relevant antigens in transplantation (human leukocyte antigen, major histocompatibility complex class I chain-related gene A and killer cell immunoglobulin-like receptor) and transfusion (blood group and human platelet antigens) medicine in Māori and Polynesians. This report sets these data in context and highlights allelic variations and their implications for ancestry and health. It is hoped that this information may help to resolve some of the present inequalities in Māori and Pacific health status.